Basic and Advenced Care of Polytraumatized Patients - Espinoza, José Miguel (2011)
Trauma has now become a pandemic with a severe social en economical impact upon society. High morbidity and mortality rates; and especially the high costs of frequent permanent sequels of trauma, put pressure on healthcare systems for facing this condition using a multidisciplinary approach, looking for minimizing damage using multiple strategies. In this respect, healthcare systems must be adequately organized as well as all the processes in order to achieve good outcomes when taking care of polytraumatized patients; consequently, healthcare teams must be adequately prepared, always looking for continuous training and updating with respect to initial management of these patients, since, according to many studies, mortality rates reach the highest values during the first hour after the event, and 25% of deceases occur because of an inadequate management.